2001
DOI: 10.1111/j.1540-5915.2001.tb00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Information Sequence and Irrelevant Distractor Information When Using a Computer‐based Decision Aid*

Abstract: Computer-based decision aids are intended to support and improve human judgments. Frequently, the largest portion of the design effort is devoted to the technical aspects of the system; behavioral aspects are often overlooked. As a result, the decision aid may be ineffective. An experiment was conducted to examine the effects of two information structure variables that theoretically affect judgments: information sequence and irrelevant distractor information. Auditor subjects made continuing existence judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…As another possibility, which could only be completed with a larger number of students, an additional group could train on ICS2, then use ICS1 for the next phase of the testing, and then complete Phase III with the other groups. This would indicate a test situation that is consistent with the findings of Reneau and Blanthorne (2001) by providing active, diagnostic explanations later in the process. Future development of the systems tested in this study could also include expanding the systems for use with other audit cycles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As another possibility, which could only be completed with a larger number of students, an additional group could train on ICS2, then use ICS1 for the next phase of the testing, and then complete Phase III with the other groups. This would indicate a test situation that is consistent with the findings of Reneau and Blanthorne (2001) by providing active, diagnostic explanations later in the process. Future development of the systems tested in this study could also include expanding the systems for use with other audit cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The experts involved in the study used explanations for verifying their solutions, which is a more active approach. Reneau and Blanthorne (2001) found that judgment is more accurate when diagnostic information in a decision aid is presented later in the process, and when no irrelevant distraction information is presented. Finally, Mascha (2001) found that the task complexity as well as type of feedback affects the acquisition of procedural knowledge, with task complexity playing a more important role.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…2 The dilution effect has also been shown to occur in a legal context (Smith, Stasson, andHawkes 1998/1999) and in consumer behavior (Meyvis and Janiszewski 2002). Other accounting studies that have examined the dilution effect include Reneau and Blanthorne (2001), Waller and Zimbelman (2003), Seow (2009), Wood (2012), and Fanning et al (2015). Waller and Zimbelman (2003) provide a review of the dilution literature in accounting.…”
Section: Introductionmentioning
confidence: 99%
“…The use of decision aids is widespread in accounting (Dowling and Leech, 2007;Mascha and Smedley, 2007), health care (Holbrook et al, 2007;Inger, 2007; McMaster University Evidence-based Practice Center, 2002;Miller, 1994), human-resource management (Lawler and Elliot, 1996;Sturman, Hannon, and Milkovich, 1996) and marketing (Haubl and Trifts, 2000;Olson and Widing II, 2002;Wierenga, Van Bruggen, and Staelin, 1999). Increasingly, computerized decision aids are developed to support human judgments (Bell, Bedard, Johnstone, and Smith, 2002;Brown and Eining, 1997;Dowling and Leech, 2007;Mascha and Smedley, 2007;Reneau and Blanthorne, 2001;Wheeler and Jones, 2006). Technology offers the opportunity to have more discretion regarding the design of computerized decision aids as compared with manual decision aids.…”
Section: Introductionmentioning
confidence: 99%